2006
DOI: 10.1007/s00270-005-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wall Shear Stress Changes in Arteries and Veins of Arteriovenous Polytetrafluoroethylene Grafts Using Magnetic Resonance Imaging

Abstract: The purpose of the study was to determine simultaneously the temporal changes in luminal vessel area, blood flow, and wall shear stress (WSS) in both the anastomosed artery (AA) and vein (AV) of arteriovenous polytetrafluoroethylene (PTFE) grafts. PTFE grafts were placed from the iliac artery to the ipsilateral iliac vein in 12 castrated juvenile male pigs. Contrast-enhanced magnetic resonance angiography with cine phase-contrast magnetic resonance imaging was performed. Luminal vessel area, blood flow, and WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 10 publications
3
45
1
1
Order By: Relevance
“…To assess hemodynamic changes and vascular remodeling of the vein-to-graft anastomosis and control vessels, MRI was performed as previously described (35,40). Animals were anesthetized for the procedure as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess hemodynamic changes and vascular remodeling of the vein-to-graft anastomosis and control vessels, MRI was performed as previously described (35,40). Animals were anesthetized for the procedure as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has been especially interested in the effect of WSS (the dragging force of the blood on the endothelium) because we and others have shown that it is increased at the vein-to-graft anastomosis of hemodialysis grafts (11,40) and because it regulates the expression of many proteins including MMP-2, MMP-9, VEGF-A, and VEGF receptor (VEGFR)-2 (1,53,58). Recently, there have been several reports describing the use of phase-contrast magnetic resonance angiography with MRI (PC MRA/MRI) to determine blood flow and luminal vessel area to estimate WSS (3,33,40,44). Thus, our overall hypothesis is that the formation of intimal hyperplasia resulting in venous stenosis is in part related to changes in WSS that results in the activation of matrix regulatory proteins causing subsequent venous stenosis formation.…”
mentioning
confidence: 99%
“…Large-animal models are advantageous because they have vessel anatomy similar to that of humans and provide the opportunity to study in detail hemodynamics and histology, but also allow for testing of experimental drug therapies and devices. The main large-animal models to date in dialysis access have been porcine models (47,64,65). One main disadvantage of both small and large animal models is the inability to simulate the long-term effects and consequences of CKD and endothelial dysfunction.…”
Section: Future Perspectives: New Frontiers In Vascular Access Researmentioning
confidence: 99%
“…Hemodynamic sheer stresses play a significant role in development of neointimal hyperplasia 87,112,206,207 . Therefore, altering the sheer stress pattern to prevent turbulent, lowflow, and low-sheer stresses could reduce the development of neointimal hyperplasia.…”
Section: Improving Hemodynamicsmentioning
confidence: 99%
“…In order to advance the field further, we need to further our current understanding of both the clinical and experimental pathways that result in venous neointimal hyperplasia and mechanisms that lead to biofilm and fibrin sheath production in C V C s b y u s i n g t h e a d v a n c e d technologies and tools in cellular and molecular biology, bioengineering, genomics, proteomics, and vascular imaging (ultrasound, computed tomography, and magnetic resonance imaging) 65,124,214 . Finally, small and large animal models of AVF and AVG, which a number of investigators in this field have already developed 61,93,207,[215][216][217] , will play an essential role in "translating" our knowledge of pathophysiologic mechanisms in vascular access dysfunction to novel therapies for patients.…”
Section: Future Perspectives: New Frontiers In Researchmentioning
confidence: 99%